Bridging Divides in Digital Pedagogy: A Narrative Review of Emerging Tools and Inclusive Practices - Masripah; Anisah, Ani Siti; Usman, Asep Tutun (Eduscape : Journal of Education Insight, 2025)
This study presents a narrative review of digital pedagogy and technology-enhanced learning, focusing on how emerging tools and pedagogical strategies influence higher education. The review analyzes both opportunities and challenges of integrating digital technologies into teaching and learning. A systematic methodology was applied, drawing on peer-reviewed literature indexed in Scopus, Web of Science, and Google Scholar, with keywords such as digital pedagogy, technology-enhanced learning, artificial intelligence in education, AR/VR in education, and digital divide. The inclusion criteria covered empirical studies, reviews, and case studies published between 2015 and 2025. The results highlight that artificial intelligence supports personalization and predictive learning outcomes, while augmented and virtual reality enhance student motivation and comprehension through immersive experiences. Teacher digital competence emerged as a decisive factor for successful adoption, yet disparities remain between developed and developing contexts. Inclusive and human-centered pedagogy plays a crucial role in ensuring equitable access, particularly for learners with diverse needs. Despite these benefits, systemic barriers such as infrastructural deficiencies, insufficient professional training, and ethical concerns about data privacy continue to limit implementation. To address these issues, the discussion emphasizes the importance of supportive policy frameworks, collaborative partnerships, and targeted investments. Future research should explore longitudinal and comparative perspectives to understand the long-term impact of digital pedagogy across diverse contexts. Overall, the findings stress the urgency of developing inclusive and sustainable strategies to ensure technology reduces, rather than deepens, educational inequities.